Cumulation Across Attitudes and Plural Projection. (18th August 2020) - Schmitt, Viola
Abstract: This paper investigates cumulative readings of sentences in which some, but not all of the plural expressions have a de dicto reading, i.e. sentences where the lower plural is interpreted in the scope of an attitude verb like believe . I argue that such cases represent a problem for existing accounts of cumulativity, because the required cumulative relation cannot be formed. I then motivate and propose an alternative analysis where all plural expressions are interpreted in situ : I expand the 'plural projection' framework put forth by Haslinger & Schmitt (2018, 2019), Schmitt (2019), where embedded pluralities 'project' to the denotations of higher nodes in the sense that the latter reflect the part-structure of the former and where cumulativity is derived via a compositional rule in a step-by-step fashion. I show that if the denotations of the plurals with the de dicto construal are analyzed as pluralities of individual concepts, which project in the afore-mentioned sense to pluralities of propositions, the data can be explained straightforwardly. This proposal differs from treatments in terms of collective belief that don't appeal to pluralities of propositions ( Pasternak 2018a, b ), in that it (i) arguably generalizes to a larger number of examples and (ii) links grammatical plurality in the embedded clause to the availability of cumulative readings.